A reconfiguração da Federação Nacional das Apaes (Fenapaes) no estabelecimento da relação entre público e privado nas políticas de educação especial (1974/2016) - Lehmkuhl, Márcia de Souza (2018)
This study aimed to investigate the trajectory of the relationship between the public and private sectors in the field of special education in Brazil through the discourses produced by the National Federation of Associations of Parents and Friends of the Exceptional (Fenapaes) from 1974 to 2016. This study is justified because we believe Fenapaes has become one of the largest institutional networks in the country over the years, congregating more than 2,000 Apae units spread throughout the national territory. In order to develop such analysis, we primarily used discourses published on the journal Mensagem da Apae, which is the official Fenapaes press organ, from 1974 to 2016. We also reviewed other Federation documents as subsidiary sources, as well as governmental legislation and documentation. Our research was based on the principles of historical-dialectical materialism, particularly the contributions of Gramsci (1968, 1978, 2001, 2014) regarding the categories Unitary (Integral) State, Civil Society, Hegemony, Private Apparatuses of Hegemony, Party and Organic Intellectual. For the analysis of the magazines we search for the contributions of Cruz and Peixoto (2007. The analyses concerning special education were based on studies by Jannuzzi (1985, 2004, 2006), Bueno (1993, 2004, 2011), Jannuzzi and Caiado (2013), Rafante (2006, 2011, 2015) and Silva (1995). In order to analyze the relationship between public and private, we sought the contributions of Fontes (2006, 2010, 2017), Peroni (2003, 2008, 2009) and Montaño (2008, 2010, 2014). Based on the referenced categories and their relationship with the empirical material, we chose three axes of analysis: philanthropy, funding and organization of Fenapaes, which constituted the chapters of our thesis. The study showed that philanthropy and charity are principles that guided the field of special education during the investigated period, including the political propositions of inclusive education and ongoing funding by the public administration of the Apaes' private-philanthropic institutions, who have gained hegemony in the offering of specialized educational assistance, as service providers. Throughout this process, Fenapaes has taken the political and administrative lead of all Apae units, adjusting itself to neoliberal political directions, expressed by privatization and publicization policies that transferred part of the obligations of the State in the social field to private institutions of the "third sector". This growing prominence confirmed the hypothesis that the Apaes movement, coordinated by its National Federation, and initially characterized by the defense of the rights of people with disabilities, has built a private-philanthropic educational system over the years, characterized not only by seeking and obtaining subsidies for its maintenance, but also for its constitution as an integral and significant part of the national policies for special education